Recent progress in fiber-based soft electronics enabled by liquid metal - Yang, Bowen; Yang, Zihan; Tang, Lixue (Frontiers in Bioengineering and Biotechnology, 2023)
Soft electronics can seamlessly integrate with the human skin which will greatly improve the quality of life in the fields of healthcare monitoring, disease treatment, virtual reality, and human-machine interfaces. Currently, the stretchability of most soft electronics is achieved by incorporating stretchable conductors with elastic substrates. Among stretchable conductors, liquid metals stand out for their metal-grade conductivity, liquid-grade deformability, and relatively low cost. However, the elastic substrates usually composed of silicone rubber, polyurethane, and hydrogels have poor air permeability, and long-term exposure can cause skin redness and irritation. The substrates composed of fibers usually have excellent air permeability due to their high porosity, making them ideal substrates for soft electronics in long-term applications. Fibers can be woven directly into various shapes, or formed into various shapes on the mold by spinning techniques such as electrospinning. Here, we provide an overview of fiber-based soft electronics enabled by liquid metals. An introduction to the spinning technology is provided. Typical applications and patterning strategies of liquid metal are presented. We review the latest progress in the design and fabrication of representative liquid metal fibers and their application in soft electronics such as conductors, sensors, and energy harvesting. Finally, we discuss the challenges of fiber-based soft electronics and provide an outlook on future prospects.